ISOLASI KUMARIN DARI BIJI PINANG (Areca catechu L.) - Ibrahim, Sanusi; Iqbal, Muhamad; Arifin, Bustanul (Jurnal Riset Kimia, 2007)
ABSTRACT Coumarin has been isolated from seed of Areca catechu L. an ethyl acetate fraction which needle crystal products at 184 –185°C. Based on thin layer chromatography analysis using n-hexane  : acetone (4 : 6) as eluent got Rf 0.6. From elemental analysis, mass spectra, ultraviolet spectra, infra red spectra, nuclear magnetic resonance spectra ( H and C NMR) ,concluded this compound was 7-hidroksi-4-metil coumarine.                                                       Keywords : Areca catechu, 7-hidroksi-4-metil kumarin.